2014
DOI: 10.3390/cells3020455
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Function and Characterization of TRPCs in Neurons

Abstract: Ca2+ entry is essential for regulating vital physiological functions in all neuronal cells. Although neurons are engaged in multiple modes of Ca2+ entry that regulates variety of neuronal functions, we will only discuss a subset of specialized Ca2+-permeable non-selective Transient Receptor Potential Canonical (TRPC) channels and summarize their physiological and pathological role in these excitable cells. Depletion of endoplasmic reticulum (ER) Ca2+ stores, due to G-protein coupled receptor activation, has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 139 publications
1
35
0
Order By: Relevance
“…In contrast, a recent report showed that STIM2 is essential for the SOCE in hippocampal neurons and downregulation of STIM2 leads to massive loss of neurons. Consistent with this, samples of AD patients also showed a decrease in STIM2, but not STIM1 (Sun et al 2014). However, still the molecular identity of the Ca 2+ channel that could contribute to these results (Orai vs TRPC) is not yet established.…”
Section: 2 Ca2+ and Neuropathophysiologysupporting
confidence: 59%
See 3 more Smart Citations
“…In contrast, a recent report showed that STIM2 is essential for the SOCE in hippocampal neurons and downregulation of STIM2 leads to massive loss of neurons. Consistent with this, samples of AD patients also showed a decrease in STIM2, but not STIM1 (Sun et al 2014). However, still the molecular identity of the Ca 2+ channel that could contribute to these results (Orai vs TRPC) is not yet established.…”
Section: 2 Ca2+ and Neuropathophysiologysupporting
confidence: 59%
“…Changes in intracellular Ca 2+ concentration stimulate a number of intracellular events and could either trigger or inhibit the cell death process (Berridge et al 2000; Putney 2003). Importantly, disturbances in Ca 2+ homeostasis have been implicated in many neurodegenerative diseases such as, PD, AD, and HD (Albers and Beal 2000; Bollimuntha et al 2005b; O’Bryant et al 2009; Zuccato and Cattaneo 2007; Zuccato and Cattaneo 2009; Sun et al 2014). It is not surprising that disturbances in Ca 2+ signaling pathways underlie neuronal loss, since many factors involved in neuronal function are dependent on Ca 2+ signaling (Berridge et al 2000; Putney 2003).…”
Section: 2 Ca2+ and Neuropathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…2 So far, the majority of studies on TRPC channels have focused on their roles in mediating Ca 2+ and Na + influx after the stimulation of phospholipase C (PLC) either by G protein-coupled receptors that signal through the G q/11 subgroup of heterotrimeric G proteins or by receptor tyrosine kinases. 3 These activities cause membrane depolarization and a sustained increase in intracellular Ca 2+ concentration ([Ca 2+ ] i ), which are important for a plethora of cellular functions in many physiological systems. 4 On the other hand, a few studies also implicated TRPC channel expression and function in intracellular membranes, 5 suggesting that very diverse cellular activities may be regulated by these channels.…”
Section: Introductionmentioning
confidence: 99%